MENUJU PARADIGMA PENELITIAN SOSIOLOGI YANG INTEGRATIF - Abdul Malik; Aris Dwi Nugroho (Jurnal Sosiologi Reflektif, 2016)
Sociology as a science which has many paradigms. Variety of existing paradigms were born by a long debate on the historical birth of sociology widely known as methodenstreit (debate of methods) that distinguish inductive and deductive methods, nomothetic ideographic sciences and sciences, value-free and solid values, and the separation of theory from praxis. The long debate generated a variety of paradigms in sociological research methodology, namely: positivism, post-positivism, constructivism, critical theory and participatory